Family-wide Structural Characterization and Genomic Comparisons Decode the Diversity-oriented Biosynthesis of Thalassospiramides by Marine Proteobacteria - Zhang, Weipeng (J Biol Chem, 2016)
The thalassospiramide lipopeptides have great potential for therapeutic applications; however, their structural and functional diversity and biosynthesis are poorly understood. Here, by cultivating 130 Rhodospirillaceae strains sampled from oceans worldwide, we discovered 21 new thalassospiramide analogues and demonstrated their neuroprotective effects. To investigate the diversity of biosynthetic gene cluster (BGC) architectures, we sequenced the draft genomes of 28 Rhodospirillaceae strains. Our family-wide genomic analysis revealed three types of dysfunctional BGCs and four functional BGCs whose architectures correspond to four production patterns. This correlation allowed us to reassess the “diversity-oriented biosynthesis” proposed for the microbial production of thalassospiramides, which involves iteration of several key modules. Preliminary evolutionary investigation suggested that the functional BGCs could have arisen through module/domain loss, whereas the dysfunctional BGCs arose through horizontal gene transfer. Further comparative genomics indicated that thalassospiramide production is likely to be attendant on particular genes/pathways for amino acid metabolism, signaling transduction, and compound efflux. Our findings provide a systematic understanding of thalassospiramide production and new insights into the underlying mechanism.